Warfarin dose requirement and cytochrome P450 2C9 and Vitamin K epoxide reductase complex subunit 1-1639 genetic polymorphisms in Thai patients - Burassakorn Subsuphan; Chatchai Chinpaisal; Manat Pongchaidecha; Wibun Phanthabordeekorn; Surawut Watana (Archives of Global Professionals, 2016)
Aims: The purposes of this study were to investigate the influence of genetic polymorphisms of cytochrome P450 2C9 (CYP2C9)FNx013 and Vitamin K epoxide reductase complex subunit 1-1639 (VKORC1-1639) G >A and patient's characteristics on warfarin dose requirement and to establish an equation for predicting the warfarin maintenance dose in Thai patients. Settings and Design: This is an observational, retrospective study in outpatients. Ninety-one outpatients receiving warfarin at Phaholpolpayuhasena Hospital, Kanchanaburi, were recruited to this study. Subjects and Methods: Whole blood, dose, and demographic data were collected. Blood samples were analyzed for the genetic polymorphism by restriction fragment length polymorphism technique. Statistical Analysis Used: Differences in baseline characteristics among genotypes were evaluated by analysis of variance or Kruskal-Wallis and the Mann-Whitney U-test or Chi-square test for parametric and nonparametric variables, respectively. Association between genetic factors and warfarin dose was based on Eta test, whereas associations between warfarin dose and polymorphisms were evaluated using Pearson correlation test. Stepwise regression was used to identify factors contributing to warfarin dose requirement followed by linear regression model to develop a warfarin dosing algorithm. Results: CYP2C9FNx011FNx011 (wild type) genotype was found in 90 patients (98.90%), and CYP2C9FNx011FNx013 was found in only 1 patient (1.10%). No CYP2C9FNx013FNx013 genotype was observed. Polymorphisms of VKORC1-1639 GG was found in 9 patients (9.89%) while GA and AA genotype were found in 30 patients (32.97%) and in 52 patients (57.14%), respectively. Patients with VKORC1-1639 AA genotype required statistically and significantly lower, average weekly warfarin dose (19.97 ± 7.61 mg) than GG genotype (37.89 ± 12.20 mg) and GA genotype (29.48 ± 11.50 mg) with the P < 0.05. Conclusions: Using stepwise multiple linear regression, VKORC1-1639 AA, age, and weight could explain about 45.3% of the variation of warfarin maintenance dose. Multivariate analysis of the equation indicated a significant negative correlation between warfarin dose and VKORC1-1639 AA and age, but a significant positive correlation between warfarin dose and weight. This suggested that VKORC1 genotyping may be more important in warfarin dose adjustment and should be a priority for genotype measurement.